2018
DOI: 10.3390/ijerph15061205
|View full text |Cite
|
Sign up to set email alerts
|

Reloading Pupils’ Batteries: Impact of Green Spaces on Cognition and Wellbeing

Abstract: Cognitive functioning and academic performance of pupils depend on regular breaks from classroom work. However, it is unclear which settings during such breaks provide the best environment to restore cognitive performance and promote wellbeing of adolescent pupils. Therefore, we investigated the effects of staying in different urban green spaces during breaks. Sixty-four pupils (16–18 years old) participated in a cross-over experiment. They were placed into one of three settings (small park, larger park, fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Nevertheless, the many strands of environmental education at least hold an implicit assumption that humans’ wellbeing is interconnected with the wellbeing of the natural environment [ 51 ]. Furthermore, many studies link various concepts of connecting with nature and individual wellbeing [ 17 , 18 , 20 , 53 , 54 , 55 ], particularly within the educational setting [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Environmental and Sustainability Educationmentioning
confidence: 99%
“…Nevertheless, the many strands of environmental education at least hold an implicit assumption that humans’ wellbeing is interconnected with the wellbeing of the natural environment [ 51 ]. Furthermore, many studies link various concepts of connecting with nature and individual wellbeing [ 17 , 18 , 20 , 53 , 54 , 55 ], particularly within the educational setting [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Environmental and Sustainability Educationmentioning
confidence: 99%
“…Recreation might be the most important non-timber service provided by forests (Elsasser 1996;Meyer et al 2019). Forest visitors significantly increase their well-being by several factors (Wallner et al 2018). Additionally, tourism can trigger considerable income for communities adjacent to larger forests (Job 2008;Mayer and Woltering 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although restoration research has shown that natural environments achieve higher outcomes concerning the improvement of the psychological and physiological state of humans than built environments (e.g., Ulrich et al 1991;Hartig & Staats 2006;Van den Berg et al 2003;Tyrväinen et al 2014;Wallner et al, 2018), little is known about the health benefits of natural and semi-natural mountain landscape types compared to blue (rivers, lakes) and grey (urban built-up areas) spaces. In addition, only few studies tested the relationships between human health and well-being and natural environments with varying levels of land use intensities and plant and animal biodiversity.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Restoration research has shown that natural environments achieve higher outcomes concerning the improvement of the psychological and physiological state of humans than urban or built environments (e.g. Ulrich et al, 1991;Parsons et al, 1998;Staats et al, 2003;van den Hartig & Staats, 2006;Lee et al 2009;Berg et al, 2010;Tyrväinen et al, 2014;Wallner et al, 2018). In this context the impression and/or the experience of nature and natural elements were found to be important drivers for restoring the cognitive functions of humans (Berman et al, 2008(Berman et al, , 2012Berto, 2005;Kaplan & Kaplan, 1989) and their physical and mental health (Bratman et al, 2012;Keniger et al, 2013).…”
Section: Linkages Between Ecosystem Services and Biodiversitymentioning
confidence: 99%